DETERMINANTS OF THE CHILDREN INTENTION TO CONSUME FAST FOOD PRODUCTS - Wiharto, Bambang; Haryanto, Jony Oktavian (UI Scholars Hub, 2009)
Children are unique and also potential market because they usually do not spend their own money but they have a huge purchasing power through their parents. They are potential market, because from the number of kids in the market and their spending are big and promising. There are three types of kids market: first, children as the primary markets; second, children as the influencer market which emphasizing on the influence of children assert on family purchases. Third, because the children will grow up, then we can consider children as the future market. Based on the above descriptions, the authors intent to identify the determinants of children intention to consume such as product characteristics, reference group, retail environment and promotion, and create a questionnaire for the children and develop hypothesis using these study findings. The data obtained from the field using survey method was used to test all the hypotheses empirically. Based on the research findings, we came to conclusion that the promotion has a greater and important effect in developing intention of children’s consumption. These initial findings will be used intentionally in another study which is try to find out the relationship between children intention to consume and their commitment to future market as they grown up and second objective of this study is to develop an initial and appropriate questionnaire for the children which we realize is different from questionnaire for the adult people.